assignment 8

course MTH 164

Your work has been received. Please scroll through the document to see any inserted notes (inserted at the appropriate place in the document, in boldface) and a note at the end. The note at the end of the file will confirm that the file has been reviewed; be sure to read that note. If there is no note at the end, notify the instructor through the Submit Work form, and include the date of the posting to your access page.

Student Name: Daniel Drayerassignme 008. Identities Initials: DRD Date and Time 02-26-2006 11:23:12

......!!!!!!!!...................................

11:30:59 `q001. Note that there are four questions in this Assignment. In general the sine and cosine functions and tangent function are defined for a circle of radius r centered at the origin. At angular position theta we have sin(theta) = y / r, cos(theta) = x / r and tan(theta) = y / x. Using the Pythagorean Theorem show that sin^2(theta) + cos^2(theta) = 1.

......!!!!!!!!...................................

RESPONSE --> The hypotenuse^2 = Opposite^2 + Adjacent^2, Also, Sin(theta) is the Opposite/Radius(1) and Cos(theta) is the Adjacent/Radius(1) This is can be written as: Sin^2(theta) + Cos^2(theta) = Radius^2 since the radius is known to be 1, we can write it as Sin^2(theta) + Cos^2(theta) = 1

.................................................

......!!!!!!!!...................................

11:32:54 The Pythagorean Theorem applies to any point (x,y) on the unit circle, where we can construct a right triangle with horizontal and vertical legs x and y and hypotenuse equal to the radius r of the circle. Thus by the Pythagorean Theorem we have x^2 + y^2 = r^2. Now since sin(theta) = y/r and cos(theta) = x/r, we have sin^2(theta) + cos^2(theta) = (y/r)^2 + (x/r)^2 = y^2/r^2 + x^2/r^2 = (y^2 + x^2) / r^2 = r^2 / r^2 = 1.

......!!!!!!!!...................................

RESPONSE --> okay, I see what we did here.

.................................................

......!!!!!!!!...................................

12:03:12 `q002. Using the fact that sin^2(theta) + cos^2(theta) = 1, prove that tan^2(theta) + 1 = sec^2(theta).

......!!!!!!!!...................................

RESPONSE --> Sec^2(theta) = (hypotenuse/adjacent)^2 Tan^2(theta) + 1 = (sin(theta)/cos(theta))^2 + 1 =sin^2(theta) / cos^2(theta) + 1 =sin^2(theta)/cos^2(theta) + cos^2(theta)/cos^2(theta) =(sin^2(theta) + cos^2(theta)) / cos^2(theta) =1/cos^2(theta) = sec^2(theta)

.................................................

......!!!!!!!!...................................

12:05:54 Starting with tan^2(theta) + 1 = sec^2(theta) we first rewrite everything in terms of sines and cosines. We know that tan(theta) = sin(theta)/cos(theta) and sec(theta) = 1 / cos(theta). So we have sin^2(theta)/cos^2(theta) + 1 = 1 / cos^2(theta). If we now simplify the equation, multiplying both sides by the common denominator cos^2(theta), we get sin^2(theta)/cos^2(theta) * cos^2(theta)+ 1 * cos^2(theta)= 1 / cos^2(theta) * cos^2(theta). We easily simplify this to get sin^2(theta) + cos^2(theta) = 1, which is thus seen to be equivalent to the original equation tan^2(theta) + 1 = sec^2(theta).

......!!!!!!!!...................................

RESPONSE --> check

.................................................

......!!!!!!!!...................................

12:11:12 `q003. Prove that csc^2(theta) - cot^2(theta) = 1.

......!!!!!!!!...................................

RESPONSE --> csc^2(theta) - cot^2(theta) = 1 1 = 1/sin^2(theta) - cos^2(theta)/sin^2(theta) =(1 - cos^2(theta))/sin^2(theta) since 1 - cos^2(theta) = sin^2(theta) 1 = sin^2(theta)/sin^2(theta)

.................................................

......!!!!!!!!...................................

12:12:10 Rewriting in terms of sines and cosines we get 1 / sin^2(theta) - cos^2(theta)/sin^2(theta) = 1. We now multiply through by the common denominator sin^2(theta) to get 1 / sin^2(theta) * sin^2(theta) - cos^2(theta)/sin^2(theta) * sin^2(theta) = 1 * sin^2(theta), or 1 - cos^2(theta) = sin^2(theta). This is easily rearranged to give us sin^2(theta) + cos^2(theta) = 1, which we know to be true. The original equation is thus equivalent to this true equation, and is therefore true.

......!!!!!!!!...................................

RESPONSE --> check

.................................................

......!!!!!!!!...................................

12:26:36 `q004. Prove that sec^2(theta) * csc^2(theta) - csc^2(theta) = sec^2(theta).

......!!!!!!!!...................................

RESPONSE --> [1/cos^2(theta) * 1/sin^2(theta)] - 1/sin^2(theta) = 1/cos^2(theta) [1/cos^2(theta) * 1/sin^2(theta)] - 1/sin^2(theta) 1/[cos^2(theta) * sin^2(theta)] - 1/sin^2(theta) 1/[cos^2(theta) * sin^2(theta)] - cos^2(theta)/[cos^2(theta) * sin^2(theta)] [1 - cos^2(theta)]/[cos^2(theta) * sin^2(theta)] [1 - cos^2(theta)] = sin^2(theta) sin^2(theta)/[cos^2(theta) * sin^2(theta)] = 1/cos^2(theta) = sec^2(theta)

.................................................

......!!!!!!!!...................................

12:27:47 Rewriting in terms of sines and cosines we get 1/cos^2(theta) * 1 / sin^2(theta) - 1/sin^2(theta) = 1/cos^2(theta). We now multiply through by the common denominator sin^2(theta)* cos^2(theta) to get sin^2(theta)* cos^2(theta) * 1/cos^2(theta) * 1 / sin^2(theta) - sin^2(theta)* cos^2(theta) * 1/sin^2(theta) = sin^2(theta)* cos^2(theta) * 1/cos^2(theta). Simplifying we get 1 - cos^2(theta) = sin^2(theta), which we rearrange to get sin^2(theta) + cos^2(theta) = 1. Note that there are other strategies for proving identities, which you will see in your text.

......!!!!!!!!...................................

RESPONSE --> I probably used the other strategy, check

You took a different route through the algebra on that last one, but it's equally valid and actually more sophisticated than the given solution. Good work

Let me know if you have questions.